Strategic planning of human resources in crisis situations : https://doi.org/10.5937/etp2501001P - Parojčić, Danijela; Milićević, Srđan; Parojčić, Aleksa (Ekonomija - teorija i praksa, 2025)
Strategic planning of human resources in crisis situations is a key process for ensuring the resilience and competitive advantage of organizations under conditions of uncertainty. This paper explores the effectiveness of strategic approaches to human resource management during economic disruptions, technological changes, and global crises. The focus is on proactive risk recognition, development of crisis teams, continuous employee education, and the improvement of leadership skills, all of which contribute to business stability. Special attention is given to the implementation of innovative work models, such as digitization and flexible work arrangements, which support business continuity and maintain productivity. The paper also emphasizes the importance of fostering psychological safety for employees and creating an organizational culture that promotes innovation and transparent communication. Research shows that trust between management and employees, along with the development of expert and leadership teams, significantly contributes to the rapid adaptation of organizations in crisis situations. The results of the analysis indicate that strategic human resource planning during crises ensures the long-term sustainability of organizations through flexibility, innovation, and resilience. These elements form the foundation for successfully overcoming challenges in turbulent times.